Preparation method and application of lithium manganese iron phosphate positive electrode material
Through the method of continuous grinding and spray drying of multiple feedings, the problem of difficult to take into account the conductivity and compaction density of lithium manganese iron phosphate positive electrode material is solved, and efficient material preparation and battery performance are achieved.
Patent Information
- Application Number
- CN202411369020.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
The ionic and electronic conductivity of lithium manganese iron phosphate cathode material has poor ionic and electronic conductivity, low compaction density, and it is difficult to take into account both the electrochemical performance and compaction density.
Using the preparation method of continuous grinding of multiple feeding, the lithium source, phosphorus source and carbon source are first ground, and then iron source and manganese source are added in batches, spray-drying and calcining under an inert atmosphere, and finally crushing to achieve full carbon source. Covering and particle grading improve the compaction density and conductivity of the material.
The compaction density and conductivity of lithium manganese iron phosphate positive electrode material are improved, the energy density and cycle stability of the battery are enhanced, and the process is simple, environmentally friendly and low cost.
Smart Images

Figure BDA0005067173290000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method and application of a lithium manganese iron phosphate positive electrode material. Background Art
[0002] Lithium manganese iron phosphate (LiFeMnPO4, LMFP) is a new type of lithium-ion battery material that combines the high safety of lithium iron phosphate (LiFePO4, LFP) and the high voltage characteristics of lithium manganese phosphate. In addition, due to the presence of manganese, LMFP generally has a higher operating voltage and higher energy density than LFP. Therefore, LMFP has attracted widespread attention due to its environmental friendliness, high energy density and cycle stability, which broaden the potential applications of LMFP in electric vehicles and portable electronic devices. However, there are still many challenges in the research and development of LMFP. First, when the manganese content is too high, due to the Jahn-Teller effect, manganese ions are easily dissolved and deposited on the surface of the negative electrode during the charge and discharge process, destroying the SEI film, causing the SEI film to continuously regenerate and repair, thereby consuming a large amount of active lithium and causing capacity loss. Secondly, the LiFeMnPO4 battery has an intrinsically low Li + The diffusion coefficient and electronic conductivity cause obvious polarization phenomenon during high-rate (≥5C) charging and discharging, resulting in low capacity retention and poor rate performance.
[0003] The main modification methods of LMFP include nano-sizing, carbon coating and metal ion doping. Reducing the particle size to nanoscale by mechanical ball milling and other methods can shorten the lithium ion migration path, improve the material activity, and thus obtain excellent electrochemical performance. The carbon coating is uniformly coated on the surface of LMFP particles. On the one hand, the carbon layer can form a continuous conductive network, which can improve the conductivity of the composite material as a whole; the carbon layer can also increase the electrochemical active area of the material, avoid particle agglomeration, improve uniformity, improve the lithium ion transmission rate, and thus enhance the battery rate performance; on the other hand, the carbon layer after surface coating can serve as a stable interface, which can inhibit the dissolution of manganese ions to a certain extent, which helps to improve the cycle stability and service life of the battery. However, the coating of the carbon layer is not conducive to improving the compaction density of lithium manganese iron phosphate. Therefore, how to take into account the performance of LMFP positive electrode materials is a technical problem that needs to be solved urgently in this field.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for preparing a lithium iron manganese phosphate positive electrode material to solve the technical problems existing in the prior art that the lithium iron manganese phosphate material has poor ionic and electronic conductivity, low compaction density, or the electrochemical performance and compaction density cannot be taken into account; the method of the present invention can not only improve the compaction density and conductivity of the lithium iron manganese phosphate material, but also has a simple process, is easy to implement, and is environmentally friendly and pollution-free.
[0006] The second object of the present invention is to provide a use of the lithium iron manganese phosphate positive electrode material prepared by the preparation method of the lithium iron manganese phosphate positive electrode material as described above in the preparation of lithium ion batteries.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] A method for preparing a lithium manganese iron phosphate positive electrode material comprises the following steps:
[0009] A lithium source, a phosphorus source and a carbon source are added to a solvent and ground to obtain slurry A. An iron source and a manganese source are added to the slurry A in multiple times, and a grinding operation is performed after each addition of the iron source and the manganese source. After the iron source and the manganese source are all added, spray drying, calcination and crushing are performed under an inert atmosphere to obtain the slurry.
[0010] The lithium iron manganese phosphate positive electrode material prepared by the method for preparing the lithium iron manganese phosphate positive electrode material as described above is used in preparing lithium ion batteries.
[0011] Compared with the prior art, the present invention has the following beneficial effects:
[0012] (1) The present invention adopts a preparation method of multiple feeding and continuous grinding. First, the lithium source, phosphorus source and carbon source are ground to be fully dispersed, and then the iron source and manganese source are added and ground to fully coat the carbon source. The manganese source and iron source are added and ground multiple times to achieve the size distribution of the slurry particles at the front end. This method can not only improve the compaction density and conductivity of the lithium manganese iron phosphate positive electrode material, but also is simple and easy to implement, environmentally friendly and pollution-free.
[0013] (2) The method of the present invention can not only improve the electrochemical properties of lithium manganese iron phosphate, but also improve its compaction density, which is of great significance for improving the energy density and volume energy density of the battery, and can avoid the use of complex processes and expensive equipment, and has low cost. DETAILED DESCRIPTION
[0014] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0015] A first aspect of the present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0016] A lithium source, a phosphorus source and a carbon source are added to a solvent and ground to obtain slurry A. The iron source and the manganese source are added to the slurry A in multiple times, and grinding is performed after each addition of the iron source and the manganese source. After all the iron source and the manganese source are added, spray drying, calcination and crushing are performed under an inert atmosphere to obtain the slurry.
[0017] The lithium source, phosphorus source and carbon source are first ground to be fully dispersed, and then the iron source and manganese source are added and ground to fully coat the carbon source. The manganese source and iron source are added and ground multiple times to achieve the size distribution of the slurry particles at the front end. The present invention adopts a preparation method of multiple feeding and continuous grinding, which can achieve full dispersion of the lithium manganese iron phosphate slurry, improve the utilization efficiency of the material, and can achieve uniform coating of the carbon layer and the size distribution of the slurry particles at the front end, which can not only improve the compaction density and conductivity of the lithium manganese iron phosphate positive electrode material, but also is simple and easy to implement, environmentally friendly and pollution-free.
[0018] The method of the present invention can not only improve the electrochemical properties of lithium manganese iron phosphate, such as capacity, rate performance and cycle stability, but also improve its compaction density, which is of great significance for improving the energy density and volume energy density of the battery. In addition, the method can avoid the use of complex processes and expensive equipment, reduce production costs and also reduce pollution to the environment, which is in line with the development trend of green chemistry.
[0019] In some specific embodiments of the present invention, the method for preparing the lithium manganese iron phosphate positive electrode material specifically comprises the following steps:
[0020] S1. adding a lithium source, a phosphorus source and a carbon source to part of the solvent and grinding to obtain a slurry A;
[0021] S2. Add part of the iron source, part of the manganese source and the remaining solvent to slurry A and continue grinding to obtain slurry B;
[0022] S3. Add the remaining iron source and the remaining manganese source to slurry B and continue grinding to obtain slurry C;
[0023] S4. The slurry C is spray-dried, calcined under an inert atmosphere, and crushed in sequence to obtain a lithium manganese iron phosphate positive electrode material.
[0024] The particle grading of the slurry can be achieved by adding the manganese source and the iron source twice and grinding them. The process is simple, and the prepared lithium manganese iron phosphate positive electrode material can take into account both electrochemical performance and compaction density, and has good comprehensive performance.
[0025] In some specific embodiments of the present invention, the molar ratio of iron to manganese in the slurry C obtained in step S3 is (2-8):(8-2), for example, it can be any point value among 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or a range value consisting of any two point values.
[0026] In some specific embodiments of the present invention, in the slurry C obtained in step S3, the molar ratio of lithium to phosphorus is 1.00-1.10:1, for example, it can be any point value among 1.00:1, 1.02:1, 1.04:1, 1.06:1, 1.08:1, 1.10:1, or a range value consisting of any two point values.
[0027] In some specific embodiments of the present invention, in the slurry C obtained in step S3, the molar ratio of the total amount of iron and manganese to phosphorus is 0.95-1:1, for example, it can be any point value among 0.95:1, 0.96:1, 0.97:1, 0.98:1, 0.99:1, 1:1, or a range value consisting of any two point values.
[0028] In some specific embodiments of the present invention, the mass ratio of the iron source added in step S3 to that in step S2 is 0.05-2:1, for example, it can be any point value among 0.05:1, 0.25:1, 0.5:1, 0.75:1, 1:1, 1.25:1, 1.5:1, 1.75:1, and 2:1, or a range value consisting of any two point values; if the ratio is too large, the compaction density will increase slightly, but the electrochemical performance will decrease; if the ratio is too small, the electrochemical performance will improve slightly, but the compaction density will decrease; by controlling the ratio within the above range, better comprehensive performance can be obtained.
[0029] In some specific embodiments of the present invention, the mass ratio of the manganese source added in step S3 to that in step S2 is 0.05-2:1, for example, it can be any point value among 0.05:1, 0.25:1, 0.5:1, 0.75:1, 1:1, 1.25:1, 1.5:1, 1.75:1, and 2:1, or a range value consisting of any two point values; if the ratio is too large, the compaction density will increase slightly, but the electrochemical performance will decrease; if the ratio is too small, the electrochemical performance will improve slightly, but the compaction density will decrease; by controlling the ratio within the above range, better comprehensive performance can be obtained.
[0030] In some specific embodiments of the present invention, the average particle size D50 of slurry B satisfies 0.38μm≤D50<0.40μm. For example, the average particle size D50 of slurry B can be any point value among 0.38μm, 0.385μm, 0.39μm, 0.395μm, or a range value consisting of any two point values.
[0031] In some specific embodiments of the present invention, the average particle size D50 of slurry C satisfies 0.40μm≤D50≤0.45μm. For example, the average particle size D50 of slurry C can be any point value among 0.40μm, 0.41μm, 0.42μm, 0.43μm, 0.44μm, 0.45μm, or a range value consisting of any two point values.
[0032] In some specific embodiments of the present invention, the difference between the average particle size D50 of slurry C and the average particle size D50 of slurry B is ≥ 0.02 μm, for example, it can be any point value among 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, or a range value consisting of any two point values.
[0033] In some specific embodiments of the present invention, the lithium source used includes at least one of lithium monohydrogen phosphate, lithium dihydrogen phosphate, lithium carbonate, lithium acetate and butyl lithium.
[0034] In some specific embodiments of the present invention, the phosphorus source used includes at least one of lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate.
[0035] In some specific embodiments of the present invention, the iron source used includes at least one of ferrous sulfate, ferrous oxalate, ferric acetate, ferric phosphate and ferrous phosphate.
[0036] In some specific embodiments of the present invention, the manganese source used includes at least one of manganese sulfate, manganese acetate, manganese oxalate, manganese phosphate, manganese pyrophosphate, manganese dioxide and manganese tetraoxide.
[0037] In some specific embodiments of the present invention, the carbon source includes an organic carbon source and an inorganic carbon source.
[0038] The present invention uses a composite coating of an organic carbon source and an inorganic carbon source. Compared with traditional single carbon source coating, the composite carbon source coating method of the present invention can better balance the electrical conductivity and compaction density of the material. By optimizing the carbon layer coating process, it can not only ensure the stable interface effect of the carbon layer, inhibit the dissolution of manganese ions, and improve the cycle stability and service life of the battery, but also avoid the adverse effect of the carbon layer coating on improving the compaction density of lithium manganese iron phosphate.
[0039] In some specific embodiments of the present invention, the organic carbon source used includes at least one of glucose, sucrose, polyvinyl alcohol, polyethylene glycol, citric acid and polystyrene.
[0040] In some specific embodiments of the present invention, the inorganic carbon source used includes at least one of graphene, conductive carbon black, Super P, acetylene black and carbon nanotubes.
[0041] In some specific embodiments of the present invention, the amount of organic carbon source added is 5wt%-15wt% of the theoretical output of lithium manganese iron phosphate positive electrode material, for example, it can be any point value among 5wt%, 7wt%, 9wt%, 10wt%, 11wt%, 13wt%, 15wt% or a range value composed of any two point values.
[0042] In some specific embodiments of the present invention, the amount of inorganic carbon source added is 0.5wt%-3wt% of the theoretical output of lithium manganese iron phosphate positive electrode material, for example, it can be any point value among 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt% or a range value composed of any two point values.
[0043] In some specific embodiments of the present invention, in step S1, the time for mixing and grinding the lithium source, phosphorus source, carbon source and solvent is 1-4 hours, for example, it can be any point value among 1h, 2h, 3h, 4h or a range value consisting of any two point values.
[0044] In some specific embodiments of the present invention, the solvent used may be water. To avoid impurities, pure water is preferably used.
[0045] In some specific embodiments of the present invention, the inlet temperature of spray drying is 220-240°C, for example, it can be any point value among 220°C, 225°C, 230°C, 235°C, and 240°C, or a range value consisting of any two point values; the outlet temperature of spray drying is 90-110°C, for example, it can be any point value among 90°C, 95°C, 100°C, 105°C, and 110°C, or a range value consisting of any two point values.
[0046] In some specific embodiments of the present invention, the calcination is a two-stage calcination, the temperature of the first stage calcination is 400-600°C, the holding time is 2-4h, and the heating rate is 1-5°C / min; and / or, the temperature of the second stage calcination is 700-800°C, the holding time is 5-7h, and the heating rate is 5-15°C / min.
[0047] The present invention adopts a two-stage sintering method, which not only improves the integrity of the material crystal structure, but also can effectively control the particle size of the final product, realize the nano-sizing of the product, shorten the ion transmission path, and thus is conducive to the improvement of compaction density and the enhancement of conductivity.
[0048] In some embodiments, typically but not limiting, for example, the temperature of the first stage calcination can be any point value among 400°C, 450°C, 500°C, 550°C, 600°C, or a range value consisting of any two point values; the holding time of the first stage calcination can be any point value among 2h, 2.5h, 3h, 3.5h, 4h, or a range value consisting of any two point values; the heating rate of the first stage calcination can be any point value among 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or any two point values. the temperature of the second stage calcination can be any point value among 700°C, 720°C, 750°C, 780°C, 800°C, or a range value composed of any two point values; the holding time of the second stage calcination can be any point value among 5h, 5.5h, 6h, 6.5h, 7h, or a range value composed of any two point values; the heating rate of the second stage calcination can be any point value among 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min, or a range value composed of any two point values.
[0049] In some specific embodiments of the present invention, the average particle size D50 after crushing is 0.8-1.5 μm, for example, it can be any point value among 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.3 μm, 1.5 μm, or a range value consisting of any two point values.
[0050] A second aspect of the present invention provides use of lithium manganese iron phosphate prepared by the method for preparing a lithium manganese iron phosphate positive electrode material as described in any one of the aforementioned embodiments in preparing a lithium ion battery.
[0051] The lithium iron manganese phosphate positive electrode material prepared by the method of the present invention not only has a high compaction density, but also can improve the electrochemical performance of lithium ion batteries when used to prepare lithium ion batteries.
[0052] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.
[0053] Example 1
[0054] The method for preparing the lithium manganese iron phosphate positive electrode material provided in this embodiment comprises the following steps:
[0055] S1. Weigh 1037 g of lithium carbonate, 2806 g of lithium dihydrogen phosphate, 665 g of sucrose, 216 g of polyethylene glycol, 9 g of Super P and 10 kg of pure water and grind them in a sand mill A for 1 h to obtain slurry A;
[0056] S2. Then 1564 g of manganese dioxide, 2713 g of iron phosphate and 4 kg of pure water were weighed and added to slurry A, and the slurry was ground to an average particle size D50 of 0.38 μm to obtain slurry B;
[0057] S3. Weigh 1359 g of iron phosphate and 783 g of manganese dioxide and add them to slurry B, and continue grinding until the average particle size D50 of the slurry is 0.42 μm to obtain slurry C;
[0058] S4. The slurry C is spray-dried to obtain a lithium iron manganese phosphate precursor, with a spray inlet temperature of 240°C and an outlet temperature of 90°C; the lithium iron manganese phosphate precursor is placed in a box-type atmosphere furnace, and under the protection of a circulating nitrogen atmosphere, the temperature is first increased to 500°C at a rate of 2°C / min and calcined for 3 hours, and then the temperature is increased to 750°C at a rate of 5°C / min and calcined for 6 hours; after natural cooling, the slurry is crushed to an average particle size D50 of 1.1 μm to obtain a lithium iron manganese phosphate positive electrode material.
[0059] Example 2
[0060] Example 2 is similar to Example 1, except that the mass ratio of manganese dioxide added in step S3 to step S2 is 0.05:1, and the mass ratio of iron phosphate added in step S3 to step S2 is 0.05:1.
[0061] The specific steps include:
[0062] S1. Weigh 1037 g of lithium carbonate, 2806 g of lithium dihydrogen phosphate, 665 g of sucrose, 216 g of polyethylene glycol, 9 g of Super P and 10 kg of pure water and grind them in a sand mill A for 1 h to obtain slurry A;
[0063] S2. Then weigh 2235g of manganese dioxide, 3878g of iron phosphate and 4kg of pure water and add them to slurry A, and continue grinding until the average particle size D50 of the slurry is 0.38μm to obtain slurry B;
[0064] S3. Weigh 194 g of iron phosphate and 112 g of manganese dioxide and add them to slurry B, and continue grinding until the average particle size D50 of the slurry is 0.42 μm to obtain slurry C;
[0065] S4. The slurry C is spray-dried to obtain a lithium iron manganese phosphate precursor, with a spray inlet temperature of 240°C and an outlet temperature of 90°C; the lithium iron manganese phosphate precursor is placed in a box-type atmosphere furnace, and under the protection of a circulating nitrogen atmosphere, the temperature is first increased to 500°C at a rate of 2°C / min and calcined for 3 hours, and then the temperature is increased to 750°C at a rate of 5°C / min and calcined for 6 hours; after natural cooling, the slurry is crushed to an average particle size D50 of 1.1 μm to obtain a lithium iron manganese phosphate positive electrode material.
[0066] Example 3
[0067] Example 3 is similar to Example 1, except that the mass ratio of manganese dioxide added in step S3 and step S2 is 2:1, and the mass ratio of iron phosphate added in step S3 and step S2 is 2:1.
[0068] The specific steps include:
[0069] S1. Weigh 1037 g of lithium carbonate, 2806 g of lithium dihydrogen phosphate, 665 g of sucrose, 216 g of polyethylene glycol, 9 g of Super P and 10 kg of pure water and grind them in a sand mill A for 1 h to obtain slurry A;
[0070] S2. Then weigh 782g of manganese dioxide, 1357g of iron phosphate and 4kg of pure water and add them to slurry A, and continue grinding until the average particle size D50 of the slurry is 0.38μm to obtain slurry B;
[0071] S3. Weigh 2715 g of iron phosphate and 1565 g of manganese dioxide and add them to slurry B, and continue grinding until the average particle size D50 of the slurry is 0.42 μm to obtain slurry C;
[0072] S4. The slurry C is spray-dried to obtain a lithium iron manganese phosphate precursor, with a spray inlet temperature of 240°C and an outlet temperature of 90°C; the lithium iron manganese phosphate precursor is placed in a box-type atmosphere furnace, and under the protection of a circulating nitrogen atmosphere, the temperature is first increased to 500°C at a rate of 2°C / min and calcined for 3 hours, and then the temperature is increased to 750°C at a rate of 5°C / min and calcined for 6 hours; after natural cooling, the slurry is crushed to an average particle size D50 of 1.1 μm to obtain a lithium iron manganese phosphate positive electrode material.
[0073] Example 4
[0074] Example 4 is similar to Example 1, except that in step S3, the average particle size D50 of slurry C is 0.40 μm, and the other conditions are the same as those in Example 1.
[0075] Example 5
[0076] Example 5 is similar to Example 1, except that: in step S2, the average particle size D50 of slurry B is 0.39 μm; in step S3, the average particle size D50 of slurry C is 0.45 μm; and the remaining conditions are the same as those in Example 1.
[0077] Comparative Example 1
[0078] Comparative Example 1 is similar to Example 1, except that all raw materials are added in step S1 for mixed grinding, and after grinding to an average slurry particle size D50 of 0.42 μm, spray drying, calcination and pulverization are performed, and the other conditions are the same as those in Example 1.
[0079] Comparative Example 2
[0080] Comparative Example 2 is similar to Example 1, except that all the iron sources and all the manganese sources are added in step S2, mixed and ground until the average particle size D50 of the slurry is 0.38 μm, and then spray dried, calcined and crushed. The other conditions are the same as those in Example 1.
[0081] Comparative Example 3
[0082] Comparative Example 3 is similar to Example 1, except that all the iron sources and all the manganese sources are added in step S2, mixed and ground until the average particle size D50 of the slurry is 0.42 μm, and then spray dried, calcined and crushed. The other conditions are the same as those in Example 1.
[0083] Comparative Example 4
[0084] Comparative Example 4: 2347g of manganese dioxide, 2806g of lithium dihydrogen phosphate, 216g of polyethylene glycol and 6.6kg of pure water were mixed and ground to an average particle size D50 of 0.43μm to obtain slurry I; 4072g of iron phosphate, 1037g of lithium carbonate, 665g of sucrose and 9g of SuperP were mixed and ground to an average particle size D50 of 0.43μm to obtain slurry II, slurry I and slurry II were mixed and ground to an average particle size D50 of 0.40μm; then spray drying, calcination and pulverization were carried out, and the conditions of spray drying, calcination and pulverization were the same as those in Example 1.
[0085] Test example
[0086] The lithium iron manganese phosphate positive electrode material prepared in each embodiment and each comparative example was used to prepare a positive electrode sheet, assemble a battery, and perform a performance test. The battery assembly process and test conditions are as follows:
[0087] Battery assembly: lithium manganese iron phosphate, conductive agent, and binder are uniformly dispersed in N-methylpyrrolidone at a mass ratio of 94:3:3 to obtain electrode slurry, and the slurry is evenly coated on aluminum foil, vacuum dried at 100°C for 12 hours, and then rolled and sliced to obtain positive electrode sheets. Metal lithium is used as the negative electrode, LB315 is selected as the electrolyte, and the diaphragm is a commercial diaphragm. CR2032 button batteries are assembled in a glove box with argon as the protective gas;
[0088] Electrochemical performance test: The relevant electrochemical performance of the battery is tested by the blue electric test system. The test conditions are constant current and constant voltage charging (cut-off voltage 4.5V, cut-off current 0.05A), constant current discharge (cut-off voltage 2.5V);
[0089] Compaction density: Use FTYS-10KN automatic powder compaction density meter, weigh 1g±0.01g of sample each time, apply pressure of 3T, and maintain pressure for 30s.
[0090] The test results are shown in Table 1.
[0091] Table 1
[0092]
[0093] From the data in Table 1, it can be seen that carbon coating is conducive to the improvement of the conductivity of lithium manganese iron phosphate, and the 0.1C first efficiency is >90%. In addition, the lithium manganese iron phosphate finished product with large and small particle grading at the front end can achieve a higher compaction density (≥2.3g / cm 3 ). The lithium iron phosphate prepared in the embodiment of the present invention can have both high compaction density and excellent electrochemical performance, which is better than the comparative example.
[0094] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: A lithium source, a phosphorus source and a carbon source are added to a solvent and ground to obtain slurry A. An iron source and a manganese source are added to the slurry A in multiple times, and a grinding operation is performed after each addition of the iron source and the manganese source. After the iron source and the manganese source are all added, spray drying, calcination and crushing are performed under an inert atmosphere to obtain the slurry.
2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The specific steps include: S1. adding the lithium source, the phosphorus source and the carbon source to the solvent and grinding them to obtain the slurry A; S2. adding part of the iron source, part of the manganese source and the solvent to the slurry A and continuing grinding to obtain slurry B; S3. Add the remaining iron source and the remaining manganese source to the slurry B and continue grinding to obtain slurry C; S4. The slurry C is spray-dried, calcined under an inert atmosphere, and crushed in sequence to obtain the lithium manganese iron phosphate positive electrode material.
3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: The mass ratio of the iron source added in step S3 to that added in step S2 is 0.05-2:
1.
4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: The mass ratio of the manganese source added in step S3 to that added in step S2 is 0.05-2:
1.
5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: The D50 of the slurry B satisfies 0.38 μm≤D50<0.40 μm.
6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: The D50 of the slurry C satisfies 0.40 μm≤D50≤0.45 μm.
7. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: Meet at least one of the following characteristics: (1) The lithium source includes at least one of lithium monohydrogen phosphate, lithium dihydrogen phosphate, lithium carbonate, lithium acetate and butyl lithium; (2) the phosphorus source comprises at least one of lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate; (3) The iron source includes at least one of ferrous sulfate, ferrous oxalate, ferric acetate, ferric phosphate and ferrous phosphate; (4) The manganese source includes at least one of manganese sulfate, manganese acetate, manganese oxalate, manganese phosphate, manganese pyrophosphate, manganese dioxide and manganese tetraoxide.
8. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The carbon source includes an organic carbon source and an inorganic carbon source, and satisfies at least one of the following characteristics: (1) The organic carbon source comprises at least one of glucose, sucrose, polyvinyl alcohol, polyethylene glycol, citric acid and polystyrene; (2) The inorganic carbon source includes at least one of graphene, conductive carbon black, Super P, acetylene black and carbon nanotubes; (3) The amount of the organic carbon source added is 5wt%-15wt% of the theoretical output of the lithium manganese iron phosphate positive electrode material; (4) The amount of the inorganic carbon source added is 0.5wt%-3wt% of the theoretical output of the lithium manganese iron phosphate positive electrode material.
9. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: Meet at least one of the following characteristics: (1) The inlet temperature of the spray drying is 220-240°C, and the outlet temperature is 90-110°C; (2) The calcination is a two-stage calcination, wherein the temperature of the first stage calcination is 400-600°C, the holding time is 2-4h, and the heating rate is 1-5°C / min; and / or the temperature of the second stage calcination is 700-800°C, the holding time is 5-7h, and the heating rate is 5-15°C / min; (3) The average particle size D50 after the pulverization is 0.8-1.5 μm.
10. Use of the lithium manganese iron phosphate prepared by the method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 9 in preparing lithium ion batteries.
Citation Information
Cited By
Method for preparing high-compaction lithium manganese iron phosphate by solid phase method
CN121292394A